Back Pain and Sciatica are not the Signs of HNP (Nerve Compression) - Ali Shahab Shahab (Indoscholar, 2018)
We used to think that back pain and sciatica were the signs of HNP. In fact, each of them has distinct clinical manifestations. In the majority of nerve compression cases, back pain and sciatica are not found. Meanwhile, most of back pain and sciatica are facet syndromes. Thus, the treatment of nerve compression and facet syndrome is different. To treat nerve compression that was progressing to paralyze, about a hundred years ago, Joel Goldthwait performed decompression through laminectomy from L1 to S3. On the other hand, in 1971, Rees, who was the first surgeon to do the procedure, performed facet denervation to cure facet syndrome on 1000 patients by using scalpel and the result was satisfying. Recently, the treatment of back pain and sciatica (facet syndrome) switches over from open surgery to facet denervation by radiofrequency. In patients with back pain whose MRI show signs of HNP but do not experience motor deficit, the choice of management is also facet denervation. Moreover, according to my experience about the treatment of back pain and sciatica, the best results so far are also by facet denervation.